2020
DOI: 10.1111/jpn.13428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reducing dietary crude protein concentration and supplementation with laminarin or zinc oxide on the faecal scores and colonic microbiota in newly weaned pigs

Abstract: A 2 × 3 factorial design experiment was conducted to examine the effects of reducing dietary crude protein (CP) concentration and/or supplementation with zinc oxide (ZnO) or laminarin on faecal scores (FS) and the large intestinal microbiota post‐weaning (PW). One hundred and forty‐four pigs were assigned to (T1) 21% standard CP diet (SCP); (T2) SCP + ZnO (SCP ZnO); (T3) SCP + laminarin (SCP LAM); (T4) 18% low CP diet (LCP); (T5) LCP + ZnO (LCP ZnO); and (T6) LCP + laminarin (LCP LAM; n = 8 replicates/treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 66 publications
(82 reference statements)
4
10
0
Order By: Relevance
“…Similar to previous studies ( 28 ), overgrowth of E. coli was linked to the rise of other Proteobacteria such as D. piger in control samples, a bacteria linked to unhealthy enteric status ( 29 ) and which seems to be controlled by ZnO ( 24 ). The clear association of these and other Proteobacteria with the Ct animals clearly evidences that either both ZnO and apramycin limited their growth or that the microbiota in these treated animals exerted a competitive exclusion against these bacterial groups.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar to previous studies ( 28 ), overgrowth of E. coli was linked to the rise of other Proteobacteria such as D. piger in control samples, a bacteria linked to unhealthy enteric status ( 29 ) and which seems to be controlled by ZnO ( 24 ). The clear association of these and other Proteobacteria with the Ct animals clearly evidences that either both ZnO and apramycin limited their growth or that the microbiota in these treated animals exerted a competitive exclusion against these bacterial groups.…”
Section: Discussionsupporting
confidence: 83%
“…The results consistently evidenced the association of Zn treatment with species belonging to Ruminococcus , Eubacterium , Clostridium , Blautia , Lachnoclostridium ( Lachnoclostridium phocaeense exclusively in the core microbiota of the Zn group), and Roseburia , all from the order Eubacteriales (phylum Firmicutes , class Clostridia ). Previous studies support the presence of members of Lachnospiraceae in ZnO-based diets ( 23 , 24 ). Members of the class Clostridia such as those enriched in ZnO-treated animals are considered part of the desirable anaerobic microbiota, renowned fiber-degrading bacteria and short-chain fatty acid (SCFA) producers ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In agreement with these findings, faecal and intestinal microbial diversity was also reduced when PW diets were supplemented with pharmacological levels of ZnO, alone or in combination with antibiotics in previous studies 46 48 , although sometimes it was unaffected 35 , 49 , 50 . Conversely, it has also been reported that high doses of ZnO can even increase α-diversity index values 51 , 52 .…”
Section: Discussionsupporting
confidence: 87%
“…Some other phylotypes assigned to Frisingicoccus , Muribaculaceae, Romboutsia and Turicibacter were determined as representative ASVs to Non‐Severe cohort but not Severe cohort. Frisingicoccus was increased in the colon of pigs treated with zinc oxide supplementation (Rattigan et al, 2020). Muribaculaceae has been regarded as a beneficial bacterium due to its promotion effect on gut metabolism (Ma, Zhou, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%